Prediction of groundwater pollution diffusion path based on multi-source data fusion - Zhang, Yanhong; Huo, Xiaofeng; Luo, Yue (Frontiers in Environmental Science, 2023)
In order to improve the prediction accuracy of groundwater pollution diffusion path, this paper combines multivariate data fusion technology to predict and analyze the groundwater pollution diffusion path. Under the special two-strategy swarm game model of water pollution particle swarm, this paper introduces replication dynamics with bounded continuous time-delay. Moreover, considering the dynamic behavior in both cases of constant kernel function and exponential kernel function, the hawk-dove game model is a special case of the model we are discussing. In addition, this paper proposes a method combining leaching surface and flux concentration, and applies numerical simulation method to simulate and analyze transient leakage monitoring of similar point and line source pollution in planar two-dimensional heterogeneous aquifers. The experimental study verifies that the multivariate data fusion proposed in this paper can play an important role in the prediction of groundwater pollution diffusion path.